RUANG BERBUDAYA BETAWI KEMAYORAN - Sylvia Sylvia; Rudy Surya (Jurusan Arsitektur dan Perencanaan, 2021)
Rapid development of technology in Indonesia has made foreign culture easier to enter and this has made local culture in Indonesia less attractive to new generations. The capital city of Jakarta is the main entrance for foreign cultures to enter, one of the most affected cultures is Betawi culture. Not only due to technological developments, there are also problems with the lack of exploration of the Betawi community space that has been provided in Jakarta. As a result, Betawi culture is increasingly eroded and forgotten with a new culture and it will end up as history, which will gradually disappear from the process of future habitation., which will gradually disappear from the process of future habitation. To fix this situation, a change in the way of living is needed. Starting from changing the daily patterns of the new generation which are usually only carried out during events and in certain areas, into an activity that can invite all generations to enjoy and re-develop Betawi culture so that it is not eroded by foreign cultures. By providing a space for the Betawi community to attract and bind the interests of human current generation, a new hybrid culture can be created. Therefore, Kemayoran Betawi cultural section was designed, this new space will use everydayness and approaching methods to the problems of the existing developments by utilizing the increasingly sophisticated developments in information technology. Apart from preserving Betawi culture, this space can also be used as a provider of new jobs, recreation and education facilities for the local community. Keywords: technological development; community; Betawi culture AbstrakPerkembangan teknologi yang pesat di Indonesia, membuat budaya asing lebih mudah masuk dan hal ini menyebabkan budaya lokal menjadi kurang diminati oleh generasi baru. Ibu kota Jakarta merupakan pintu masuk utama masuknya kebudayaan asing, salah satu kebudayaan yang terpengaruh besar adalah kebudayaan Betawi. Tidak hanya akibat perkembangan teknologi saja, terdapat juga permasalahan akan kurang tereksplornya ruang komunitas Betawi yang telah disediakan di Jakarta. Akibatnya kebudayaan Betawi semakin tergerus dan terlupakan yang akan berakhir menjadi sejarah yang lama kelamaan akan menghilang diproses berhuni masa depan. Untuk mengatasi permasalahan ini, dibutuhkan perubahan cara berhuni penduduk. Dimulai dari mengubah pola keseharian generasi baru yang biasanya hanya dilakukan saat acara dan pada area tertentu saja, menjadi sebuah kegiatan yang dapat mengajak semua generasi agar dapat ikut menikmati dan mengembangkan kembali kebudayaan Betawi agar tidak tergerus oleh kebudayaan asing. Dengan memberikan sebuah wadah ruang komunitas Betawi untuk menarik dan mengikat ketertarikan masyarakat generasi sekarang, dapat memunculkan sistem berhuni dengan budaya hybrid baru. Oleh sebab itu, dirancanglah sebuah ruang berbudaya Betawi Kemayoran, dimana ruang baru ini akan menggunakan metode everydayness dan approaching terhadap permasalahan perkembangan zaman yang ada dengan memanfaatkan perkembangan teknologi informasi yang semakin canggih. Selain melestarikan kebudayaan betawi, ruang ini juga bisa digunakan sebagai penyedia sarana kerja, rekreasi, dan edukasi baru bagi masyarakat setempat.